Equation of sediment transport in Chao Phya River below Chainat dam - Lin, Chung-yih; Arbhabhirama Anat; Prida Thimakorn; Nishimura, Hitoshi; Tawatchai Tingsanchali; Asian Institute of Technology (Bangkok : Asian Institute of Technology, 1975)
The construction of the Chainat dam and the dredging work in Chao Phya River changed the river regime and caused several problems in river use such as degradation and aggradation, damage to the· foot of the hydraulic structure, difficulty in navigable use, etc. All of these problems are basically involved in sediment transport. In order to obtain well understanding in these problems, ,it is necessary to investigate the transport ability of the sediment in this river. The purpose of this study is to find on equation of sediment transport in this river. By comparing the characteristics of the Chao Phya River with the limitation in each available bed- load formulas , the Einstein-Brown equation has been select ed. The mathematical model for river degradation or aggradation can be established by combining the bed-load formula with the continuity equation. Since the stage and discharge hydrographs at different locations along the river are not available, the model for simulating the stage and discharge hydrographs has also been developed. The equation of sediment transport was found by feeding the available field data into the mathematical model so that the unknown parameters could be determined
A thesis submitted in partial fulfillment of the requirements for the Degree of Master of Engineering at the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1975
Keywords: Sediment transport -- Thailand -- Chao Phya River